Data in Search of a Theory: A Critical Examination of the Relationships Among Social Performance, Social Disclosure, and Economic Performance of U.S. Firms - Ullmann, Arieh A. (Academy of Management Review, 1985)
Arieh A. Ullmann, Data in Search of a Theory: A Critical Examination of the Relationships among Social Performance, Social Disclosure, and Economic Performance of U. S. Firms, The Academy of Management Review, Vol. 10, No. 3 (Jul., 1985), pp. 540-557